2020
DOI: 10.3389/fonc.2020.01587
|View full text |Cite
|
Sign up to set email alerts
|

NLRP3 Inflammasome From Bench to Bedside: New Perspectives for Triple Negative Breast Cancer

Abstract: The tumor microenvironment (TME) is crucial in cancer onset, progression and response to treatment. It is characterized by an intricate interaction of immune cells and cytokines involved in tumor development. Among these, inflammasomes are oligomeric molecular platforms and play a key role in inflammatory response and immunity. Inflammasome activation is initiated upon triggering of pattern recognition receptors (Toll-like receptors, NOD-like receptors, and Absent in melanoma like receptors), on the surface of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 109 publications
0
17
0
Order By: Relevance
“…Abnormal activation of TLRs can induce immune reaction in tumor cells and thereby modulate the TME ( 42 ). NOD-like receptors (NLRs) are reported to be capable of activating innate immune responses ( 43 ). NLRs play crucial roles in immune functions, metastasis and tumorigenesis ( 44 , 45 ).…”
Section: Discussionmentioning
confidence: 99%
“…Abnormal activation of TLRs can induce immune reaction in tumor cells and thereby modulate the TME ( 42 ). NOD-like receptors (NLRs) are reported to be capable of activating innate immune responses ( 43 ). NLRs play crucial roles in immune functions, metastasis and tumorigenesis ( 44 , 45 ).…”
Section: Discussionmentioning
confidence: 99%
“…The primary function of the NLRP3 inflammasome is to inducing cell pyroptosis via cleaving Gasdermin D (GSDMD) and to enhancing inflammation by releasing interleukin 1β (IL1β) and interleukin 18 (IL18) [ 7 , 10 ]. It has been demonstrated in the previous studies that the NLRP3 inflammasome and its downstream products are involved in the carcinogenesis of many cancers, including colitis-associated cancer, lung cancer, breast cancer, and melanoma [ 7 , 11 , 12 ]. In terms of CRC, it has been reported that increased susceptibility of dextran sulfate sodium (DSS)-induced colitis and colitis-associated tumorigenesis in NLRP3 −/− and IL18 −/− mice, respectively [ 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…The tumor microenvironment (TME) is the result of a multistep process characterized by reprogramming across cellular components. Different critical oncogenic processes contribute to changing the TME, such as angiogenesis, invasion/metastasis, drug resistance and chronic inflammation ( 1 ). Uncontrolled chronic inflammation has been shown to play a pivotal role in the onset and development of cancer via the up-regulation of growth factors, free radicals, prostaglandins and pro-inflammatory cytokines [interleukin (IL)-1β and IL-18] ( 2 , 3 ).…”
Section: Introductionmentioning
confidence: 99%